Assessing the validity of FOCUS-ÍS: A parent report questionnaire of functional communication development of 4-year-old children - Ösp Vilberg Baldursdóttir 1994- (2022)
Introduction: Speech-language pathologists (SLPs) need to assess children’s skills in three domains of language: content, form, and use. In Iceland, there is a shortage of assessment tools that SLPs can use to evaluate language use, which includes children’s social communication skills or how they use their communication to participate with others. This study examines the psychometric properties of an assessment tool which might address this need, Focus on Communication in Children under Six (FOCUS; Thomas-Stonell, Oddson, et al., 2012b) in the Icelandic context (FOCUS-ÍS; Thomas-Stonell, Oddson, et al., 2012a). The FOCUS is questionnaire in which parents describe their child’s ability to participate in social communication activities in their everyday life. The FOCUS items are also aligned with the International Classification of Functioning, Disability and Health for Children and Youth (ICF-CY; WHO, 2001; 2007). Aim: This thesis examines key psychometric properties of the FOCUS-ÍS for monolingual Icelandic-speaking children aged 4;0-4;11. Method: Children’s scores on a number of questionnaires and tests (N = 120; FOCUS-ÍS, Strength and Difficulties Questionnaire [SDQ], Intelligibility in Context Scale [ICS], and Children’s Communication Checklist-2 [CCC-2]) routinely used in Iceland were compared to FOCUS-ÍS total, profile scores and subscale scores to examine internal reliability, construct validity, and more specifically whether or not the FOCUS-ÍS demonstrated convergent or divergent validity compared to a direct assessment measure using a standardised developmental language test (Málfærni eldri leikskólabarna [MELB]). Relationships between the FOCUS-ÍS total score and subtest scores and other tests/questionnaires were computed. Results: The FOCUS-ÍS had high internal reliability for total score and subtest scores. There were significant correlations between the two FOCUS-ÍS subscales (Body Structure, Activities and Participation) and the CCC-2, SDQ, ICS, and MELB, showing construct validity. A significant, ...